PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Widia Agustiani; Ratih Purnama Pertiwi, Ahmad Ulin Ni’am (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to develop or create learning media in the form of animated videos for fifth-grade elementary school students in the subject of Science with the material